Back to basics (motor learning in the speed and power events) (Techniques Magazine, 2024)
Motor learning is a field of sports science that investigates the processes and factors involved in learning skills. In this section we will investigate motor skills, motor control and how we can use this science to improve the effectiveness of our skill teaching schemes.